Transformasi Dakwah Digital: Budaya dan Metodologis Perubahan Komunikasi Islami di Era Digital - Istiqomah; Hamzanwadi (P3M STID Mustafa Ibrahim Al-Ishlahuddiny Kediri Lombok Barat, 2024)
Modern civilization is characterized by unprecedented technological innovations that have resulted in major cultural shifts. Religion is still one of the main phenomena most affected by the current digital revolution. Da'wah, as one of the main principles of Islam, is no exception to this global cyber culture. In order to remain relevant and address the current needs of the Muslim community, da'wah needs to adapt to the dynamics of digitalization in today's society. This article discusses the transformation of da'wah in the era of mass media, digital communication and the internet. This research explains how the global digital revolution has opened up new avenues for da'wah that have the potential to spread the message of Islam widely. However, at the same time the digitalization of communications and the culture it builds is also experiencing an unprecedented ethical strengthening related to cyber culture, cyber ethics, hyperreality and mass cognitive dissonance. So, while it is important to ensure that the method of da'wah is relevant to today's times, it must be in full accordance with the ideals of the Qur'an and Sunnah.